2022
DOI: 10.3390/genes13091665
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes Mark Sites of Methylation Instability Associated with Ageing and Cancer

Abstract: Regulation of the epigenome is critical for healthy cell function but can become disrupted with age, leading to aberrant epigenetic profiles including altered DNA methylation. Recent studies have indicated that DNA methylation homeostasis can be compromised by the formation of DNA secondary structures known as G-quadruplexes (G4s), which form in guanine-rich regions of the genome. G4s can be recognised and bound by certain methylation-regulating enzymes, and in turn perturb the surrounding methylation architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Nevertheless, as anticipated, Raucchaus et al reported that G4s are also highly present in terms of human aging clock sites. Most importantly, the authors highlighted the comparable enrichment of G4s in the binding sites of enzymes that operate both methylation and demethylation; this supports the hypothesis that G4s may be more involved in the perturbation of DNA-methylation than in the process that promotes either hyper-or hypomethylation [48]. Similarly, Moruno-Manchon et al showed that older mice treated with G4 binders (Figure 4a,b) had enhanced senescence-associated phenotypes in their brains, and they exhibited increased cognitive deficits.…”
Section: G-quadruplexes and Dna Methylationmentioning
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, as anticipated, Raucchaus et al reported that G4s are also highly present in terms of human aging clock sites. Most importantly, the authors highlighted the comparable enrichment of G4s in the binding sites of enzymes that operate both methylation and demethylation; this supports the hypothesis that G4s may be more involved in the perturbation of DNA-methylation than in the process that promotes either hyper-or hypomethylation [48]. Similarly, Moruno-Manchon et al showed that older mice treated with G4 binders (Figure 4a,b) had enhanced senescence-associated phenotypes in their brains, and they exhibited increased cognitive deficits.…”
Section: G-quadruplexes and Dna Methylationmentioning
confidence: 52%
“…G4s can be recognized by specific proteins, including methylation-regulating enzymes [47]. As anticipated, the DNA methylation level is one of the main biological clocks that indicate the extent of aging [19], and recent reports have noted the connection between G4s and aging; this is because sites that are considered to be aging clocks are enriched with G4-forming sequences [48].…”
Section: G-quadruplexes and Dna Methylationmentioning
confidence: 87%
“…However, there are only a few studies on the involvement of G4 structures in the functioning of DNA methylation machinery [ 13 , 20 ]. Nevertheless, studies based on whole-genome sequencing data identified a correlation between CpG methylation levels and G4 formation, namely, hypomethylation of the genome in regions enriched in G4 motifs [ 21 , 22 ]. The G4 formation in the promoters of imprinted genes was revealed [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 17 Moreover, some G4s are associated with DNA methylation instability, leading to aging and cancer, which increases the potential utility of these structures in clinical studies. 18 …”
Section: Introductionmentioning
confidence: 99%